Clinical utility of digital volume pulse analysis in prediction of cardiovascular risk and the presence of angiographic coronary artery disease - Konstantinos Vakalis; Aris Bechlioulis; Katerina K. Naka; Konstantinos Pappas; Christos S. Katsouras; Lampros K. Michalis (Artery Research, 2014)
Background: Stiffness Index (SI), assessed by finger photoplethysmography (digital volume pulse analysis), has been suggested as a simple and easy measure of arterial stiffness. However, its potential association with cardiovascular risk and coronary artery disease (CAD) has been little studied. The aims of the study were to investigate the relation of SI with classical risk factors and established arterial stiffness indices and its ability to predict cardiovascular risk and the presence of angiographic CAD. Methods: We enrolled 126 consecutive patients (mean age 61 years, 74% males) with suspected stable CAD undergoing diagnostic coronary angiography. Cardiovascular risk was assessed using Framingham risk score (FRS) and the European Heart score. Carotid-femoral (PWVcf) and carotid-radial (PWVcr) pulse wave velocity and augmentation index, using applanation tonometry, and SI using finger photoplethysmography, were measured in all patients. Results: SI was positively correlated with PWVcr (p = 0.017) but not with PWVcf. Increased SI (R2 0.19, p < 0.001) was independently associated with higher diastolic blood pressure and male gender. Increased SI and PWVcf were associated with higher FRS and Heart score (p < 0.05 for all), while only higher PWVcf was associated with the presence of angiographic CAD (p = 0.007). Conclusions: SI, easily derived using finger photoplethysmography, was related to classical risk factors and peripheral arterial rather than aortic stiffness. SI and PWVcf were the only vascular indices associated with cardiovascular risk, but only PWVcf was related to the presence of coronary atherosclerosis. Further research is needed to clarify the value of this useful index of arterial stiffness in risk stratification.